ANALYSIS OF LEARNING DIFFICULTIES IN READING COMPREHENSION WITH NEUROLINGUISTIC APPROACH FOR STUDENTS WITH LEARNING DIFFICULTIES IN ELEMENTARY SCHOOL ANUBANWANGMAI SCHOOL THAILAND - Nur Az Zahra; Asep Hardiyanto; Putri Mayang Rembulan; Caitlyn Ripazel Namora; Ampol Rasusoh (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2025)
This study investigates learning difficulties in reading comprehension among primary school students using a neurolinguistic approach. The neurolinguistic approach focuses on the relationship between brain processes and language skills, aiming to align teaching strategies with how the brain processes language. A descriptive qualitative method was employed, with data collection techniques including observation, interviews, and reading comprehension tests. The research subjects consisted of fourth and fifth grade students who faced barriers in reading comprehension. The results indicated that internal factors, such as attention disorders, limited vocabulary, and difficulties in mapping sentence structures, significantly affect reading comprehension. Additionally, external factors, including inadequate teaching methods and a lack of learning media, contribute to these difficulties. The study demonstrates that neurolinguistic strategies, such as visualization, repetition, and concept mapping, can improve students' comprehension by aligning teaching with cognitive processes. The findings suggest that neurolinguistic strategies may be effectively integrated into reading instruction to address comprehension challenges, offering a promising approach for enhancing reading skills in elementary education. Keywords: Learning difficulties, reading comprehension, neurolinguistic approach, primary school